LRS Bianchi Type II Massive String Cosmological Models with Magnetic Field in Lyra's Geometry - Raj Bali; Mahesh Kumar Yadav; Lokesh Kumar Gupta (Advances in Mathematical Physics)
Bianchi type II massive string cosmological models with magnetic field and time dependent gauge function () in the frame work of Lyra's geometry are investigated. The magnetic field is in -plane. To get the deterministic solution, we have assumed that the shear () is proportional to the expansion (). This leads to , where and are metric potentials and is a constant. We find that the models start with a big bang at initial singularity and expansion decreases due to lapse of time. The anisotropy is maintained throughout but the model isotropizes when . The physical and geometrical aspects of the model in the presence and absence of magnetic field are also discussed.